2021
DOI: 10.1186/s12906-021-03446-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemical profiles of the active fraction from Prinsepia utilis Royle leaves and its anti-benign prostatic hyperplasia evaluation in animal models

Abstract: Background The Prinsepia utilis Royle leaves (P. utilis) is a folk herb used for benign prostatic hyperplasia (BPH) control by ethnic minorities for centuries in China with rich in resources. Our previous studies have confirmed the anti-BPH effect of its water extract (QCJ) and the active fraction (Fr. B) separated from the QCJ by animal test. The Fr. B from P. utilis should be a potential candidate for BPH control. Methods In this study, the chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Peng et al studied the chemical composition of P. utilis leaves, identifying 10 flavonoids, namely, quercetin‐3‐O‐α‐L‐rhamnopyranosyl‐(1 → 6)‐[α‐L‐rhamnopyranosyl‐(1 → 2)]‐β‐D‐glucopyranoside‐7‐O‐β‐Dglucopyranoside, kaempferol‐3‐O‐α‐L‐rhamnopyranosyl‐(1 → 6)‐[α‐L‐rhamnopyranosyl‐(1 → 2)]‐β‐D‐glucopyranoside‐7‐O‐β‐D‐glucopyranoside, quercetin‐3‐O‐α‐L‐rhamnopyranosyl‐(1 → 6)‐β‐D‐glucopyranoside‐7‐O‐β‐D‐glucopyranoside, kaempferol‐3‐O‐α‐L‐rhamnopyranosyl‐(1 → 6)‐β‐D‐glucopyranoside‐7‐O‐β‐D‐glucopyranoside, isorhamnetin‐3‐O‐α‐L‐rhamnopyranosyl‐(1 → 6)‐β‐D‐glucopyranoside‐7‐O‐β‐D‐glucopyranoside, kaempferol‐3‐O‐α‐L‐rhamnopyranosyl‐(1 → 6)‐[α‐L‐rhamnopyranosyl‐(1 → 2)]‐β‐D‐glucopyranoside, isorhamnetin‐3‐O‐α‐L‐rhamnopyranosyl‐(1 → 6)‐[α‐L‐rhamnopyranosyl‐(1 → 2)]‐β‐D‐glucopyranoside, quercetin 3‐O‐α‐L‐rhamnopyranosyl‐(1 → 6)‐β‐D‐glucopyranoside, kaempferol‐3‐O‐α‐L‐rhamnopyranosyl‐(1 → 6)‐β‐D‐glucopyranoside, and isorhamnetin‐3‐O‐α‐L‐rhamnopyranosyl‐(1 → 6)‐β‐D‐glucopyranoside, and demonstrating their beneficial effects on rats with benign prostatic hyperplasia 16 . Another study by Shen et al identified 60 polyphenols in P. utilis leaves, with four compounds—trans‐p‐coumaric acid‐4‐O‐β‐D‐glucopyranoside, vicenin‐2, isoschaftoside, and kaempferol‐3‐O‐(2″,6″‐di‐O‐α‐L‐rhamnopyransoyl)‐β‐D‐glucopyranoside—highlighted for their favorable pharmacokinetic properties 31 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peng et al studied the chemical composition of P. utilis leaves, identifying 10 flavonoids, namely, quercetin‐3‐O‐α‐L‐rhamnopyranosyl‐(1 → 6)‐[α‐L‐rhamnopyranosyl‐(1 → 2)]‐β‐D‐glucopyranoside‐7‐O‐β‐Dglucopyranoside, kaempferol‐3‐O‐α‐L‐rhamnopyranosyl‐(1 → 6)‐[α‐L‐rhamnopyranosyl‐(1 → 2)]‐β‐D‐glucopyranoside‐7‐O‐β‐D‐glucopyranoside, quercetin‐3‐O‐α‐L‐rhamnopyranosyl‐(1 → 6)‐β‐D‐glucopyranoside‐7‐O‐β‐D‐glucopyranoside, kaempferol‐3‐O‐α‐L‐rhamnopyranosyl‐(1 → 6)‐β‐D‐glucopyranoside‐7‐O‐β‐D‐glucopyranoside, isorhamnetin‐3‐O‐α‐L‐rhamnopyranosyl‐(1 → 6)‐β‐D‐glucopyranoside‐7‐O‐β‐D‐glucopyranoside, kaempferol‐3‐O‐α‐L‐rhamnopyranosyl‐(1 → 6)‐[α‐L‐rhamnopyranosyl‐(1 → 2)]‐β‐D‐glucopyranoside, isorhamnetin‐3‐O‐α‐L‐rhamnopyranosyl‐(1 → 6)‐[α‐L‐rhamnopyranosyl‐(1 → 2)]‐β‐D‐glucopyranoside, quercetin 3‐O‐α‐L‐rhamnopyranosyl‐(1 → 6)‐β‐D‐glucopyranoside, kaempferol‐3‐O‐α‐L‐rhamnopyranosyl‐(1 → 6)‐β‐D‐glucopyranoside, and isorhamnetin‐3‐O‐α‐L‐rhamnopyranosyl‐(1 → 6)‐β‐D‐glucopyranoside, and demonstrating their beneficial effects on rats with benign prostatic hyperplasia 16 . Another study by Shen et al identified 60 polyphenols in P. utilis leaves, with four compounds—trans‐p‐coumaric acid‐4‐O‐β‐D‐glucopyranoside, vicenin‐2, isoschaftoside, and kaempferol‐3‐O‐(2″,6″‐di‐O‐α‐L‐rhamnopyransoyl)‐β‐D‐glucopyranoside—highlighted for their favorable pharmacokinetic properties 31 …”
Section: Resultsmentioning
confidence: 99%
“…Previously, more than 44 phenolic compounds, categorized into phenolic acids, anthocyanins, flavonoids, and hydroxybenzoic acid derivatives, have been reported in different parts of P. utilis, such as flowers, leaves, fruits, stems, and seeds. [16][17][18][19] In this study, the tentative identification of MFs, extracted as described in Section 2, utilizing MS/MS data in high-resolution mode, resulted in the identification of a total of 78 compounds with a mass accuracy error below ±5 ppm.…”
Section: Tentative Identification Of Untargeted Compounds Present In ...mentioning
confidence: 99%
“…[20][21][22] Currently, it is known that PUR leaf extracts can combat allergic contact dermatitis, polyphenol extracts of the seed shell of PUR can be used as potential activators of tyrosinase, and the components of PUR flavonoids have anti-benign prostatic hyperplasia and hypoglycemic effects. [23][24][25][26] Molecular docking analysis of PUR fruits, revealed that all the fractions exhibited strong radical-scavenging activities and good inhibition of cellular reactive oxygen species generation in H 2 O 2 -induced HepG2 cells and against pancreatic lipase and α-glucosidase. 27 Leaf and seed extracts exhibited noteworthy antibacterial effects against diverse pathogenic microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…PUR oil has excellent benefits in food, medicine, and cosmetics, functions as a skin barrier for SC promotion and has potential therapeutic applications as a natural anti‐inflammatory and analgesic agent 20–22 . Currently, it is known that PUR leaf extracts can combat allergic contact dermatitis, polyphenol extracts of the seed shell of PUR can be used as potential activators of tyrosinase, and the components of PUR flavonoids have anti‐benign prostatic hyperplasia and hypoglycemic effects 23–26 . Molecular docking analysis of PUR fruits, revealed that all the fractions exhibited strong radical‐scavenging activities and good inhibition of cellular reactive oxygen species generation in H₂O₂‐induced HepG2 cells and against pancreatic lipase and α‐glucosidase 27 .…”
Section: Introductionmentioning
confidence: 99%